S SENAM KAKI DIABETIK DENGAN RESPON NEUROPATI PADA PENDERITA DIABETES MELITUS TIPE 2 DI WILAYAH KERJA PUSKESMAS SUNGAI TABUK 2 - Annalia Wardhani (Journal of Nursing Invention, 2020)
Background: Neuropathy is a chronic complication that is often found in cases of type 2 diabetes mellitus. This condition causes the need for easy and inexpensive primary care, namely diabetic foot exercises. Purpose: to analyze the relationship between diabetic foot exercises and neuropathic responses in type 2 diabetes mellitus sufferers in the work area of the Sungai Tabuk 2 public health center. Methods: This type of research used a cross sectional approach with a population of 264 people, the total sample size of 42 respondents, the sample technique used was Accidental Sampling. The instrument in this study used a questionnaire and for neuropathy responses using the Score Diabetic Neuropathy Symptoms (DNS) and data analysis using Spearmans Rho. Results: there is a relationship between diabetic foot exercise and neuropathic response in type 2 diabetes mellitus patients with a value of Ï = 0.000. Rho value = 0.756. Conclusion: the majority of categories of diabetic foot exercise did diabetic foot exercise, namely 59.5%, the majority of neuropathic responses were in the category of no neuropathy, namely 54.8%. There is a relationship between diabetic foot exercise and neuropathic response in people with type 2 diabetes mellitus with a value of Ï = 0.000. The rho value = 0.756.